The Effect of Mindfulness and Loneliness on Sense of Purpose in Individuals in the Age of Quarter Life Crisis - Athallah Akhyar Reswara; Hizmah Namira Azzahra; Muhammad Daffa Purnama Sonita; Valendra Granitha Shandika Puri (Jurnal Indonesia Sosial Sains, 2024)
Sustainable Development Goals (SDGs) represent a global effort to achieve sustainable prosperity for all, with a strong focus on the quality of the next generation, particularly the youth. The future of a nation is closely tied to the quality of its young population. Early adulthood is a crucial period for determining career paths and life goals, which directly impact personal development and self-quality. One of the critical challenges faced during this period is the quarter life crisis (QLC), characterized by confusion over life purpose. In Indonesia, data shows that more than half of youth experience QLC, typically occurring between the ages of 18 and 35. This study aims to explore the factors influencing a sense of purpose to offer effective strategies for addressing the quarter life crisis. The research was conducted using a quantitative approach with non-probability sampling and survey methods. The sample consisted of 196 respondents (71.7% female and 28.3% male). Data analysis was performed using multiple linear regression with the assistance of SPSS version 8.0 software. Results revealed that mindfulness and loneliness have a significant impact (p<0.05) on the sense of purpose in individuals experiencing QLC, with an R-squared value of 0.090, indicating a 9% influence. These findings highlight the need for targeted counseling and psychological support services to address the quarter life crisis. Providing counseling that focuses on enhancing mindfulness and reducing loneliness can help individuals strengthen their sense of purpose, ultimately enabling them to navigate this challenging life stage more effectively.